PENGARUH TEKNIK ISOLASI DNA GENOM TANAMAN TEMBAKAU TERHADAP KUALITAS DAN KUANTITAS HASIL EKSTRAKSI - Ahmad Ilham Tanzil; Wahyu Indra Duwi Fanata (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
Tobacco plants are an important plantation commodity in Indonesia. However, problems often occur in cultivation. These obstacles include abiotic and biotic stress. To overcome this problem, it is necessary to improve plant varieties through molecular-based breeding programs. This biotechnology program needs to carry out optimization research on the DNA isolation process so that the results produced can be used for further analysis. The method used uses a comparison of extraction techniques using tools and grinding with chemicals. Meanwhile, tobacco leaf samples were used with a comparison of wet samples and dry samples. From the results obtained, the treatment of the grinding method with chemicals and wet samples was able to increase the quality and quantity of DNA concentration.